Preparation of biomimetic nano-structured films with multi-scale roughness. (19th May 2016) - Shelemin, A; Nikitin, D; Choukourov, A; Kylián, O; Kousal, J; Khalakhan, I; Melnichuk, I; Slavínská, D; Biederman, H
Abstract: Biomimetic nano-structured films are valuable materials in various applications. In this study we introduce a fully vacuum-based approach for fabrication of such films. The method combines deposition of nanoparticles (NPs) by gas aggregation source and deposition of overcoat thin film that fixes the nanoparticles on a surface. This leads to the formation of nanorough surfaces which, depending on the chemical nature of the overcoat, may range from superhydrophilic to superhydrophobic. In addition, it is shown that by proper adjustment of the amount of NPs it is possible to tailor adhesive force on superhydrophobic surfaces. Finally, the possibility to produce NPs in a wide range of their size (45–240 nm in this study) makes it possible to produce surfaces not only with single scale roughness, but also with bi-modal or even multi-modal character. Such surfaces were found to be superhydrophobic with negligible water contact angle hysteresis and hence truly slippery.